ANALISIS FINANSIAL TERHADAP PRODUKTIVITAS GETAH DAN POTENSI KAYU TANAMAN KARET DARI KLON GT 1 DAN SEEDLING DI KABUPATEN SAROLANGUN - Ahyauddin, Ahyauddin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Generally, a part of forest area in Sarolangun had been used by people, especially for farming and planting activities. If the area is not driven to the real policy, it will impact to the transformation of forest area function to be gardening and farming or other economic activities. The Society tapped rubber Forest must be driven to enlarge the forest usage for wood industries and to create the job vacancy. The main purposes of this research were (1) to study financially the effort of Society Plantation Forest of tapped rubber and non tapped rubber trees. (2) to get a perspective of Society Plantation Forest development in monoculture pattern for tapped and non tapped rubber. Based on the financial analysis of Net Present Value (NPV), Net B/C and IRR at interest rate of 5%, the effort of tapped rubber had a value of Rp.299,061,000; 7.54 and 26.3% respectively. The effort of non tapped rubber had a negative value of Rp.36,982,000; 0.59 and unworthy bussiness. The annual average value of income and the effort scale of tapped rubber was Rp.16,473,487 and 3 hectares respectively. From the research results, it can be suggested that: (1) for the non tapped rubber effort it should be better if the people select seedlings from a clone that can make the wood quality better to obtain the higher selling price. (2) it is suggested that in the year before the rubber trees produce latex, it should be better to plant the area with agricultural crops and vegetables to optimalize the land usage and to provide added value to the farmers.